PERAN IBU RUMAH TANGGA BEKERJA DALAM KETAHANAN PANGAN RUMAH TANGGA DI KECAMATAN UMBULHARJO - Nurindah Sari; Retno Lantarsih; Artita Devi Maharani (Fakultas Pertanian UST, 2022)
This research aimed to find out the role of working housewives in efforts to realize household food security and analyze the characteristic relationship of working housewives and their role in supporting household food security in Umbulharjo Subdistrict. This study was conducted by distributing questionnaires to 100 respondents using the Propotional Random Sampling method. The samples in this study were the working housewives in the Village of Umbulharjo Subdistrict of Yogyakarta City. The basic method of research was quantitative descriptive method. The analysis methods in this study were actors indicators (Authority, Confidence and Competence, Trust, Opportunity, Responsbility, Suppport) and simple correlation analysis with correlation coefficient test (r). The results of this study showed that the largest role of working housewives was the role in authority and responsibility, while the characteristic relationship that influences the role of housewives in supporting household food security in Umbulharjo Subdistrict is maternal education, maternal income and family income.